Inovasi Pembelajaran Di Masa COVID-19: Pelatihan Pengembangan Media Pembelajaran Di SMK Cendikia Kota Cirebon - Sandy Eka Permana; Ade Rizki Rinaldi; Mulyawan (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Cendikia Vocational School, located in Cirebon City, is the main partner in this service. As a vocational high school, they faced various obstacles during the pandemic. One of them is the sudden shift from face-to-face learning to distance learning. This creates challenges in providing quality learning experiences. In some cases, students have difficulty accessing materials and interacting with teachers, which affects learning effectiveness. This Community Service highlights the importance of innovation in learning amidst the COVID-19 pandemic. Learning media development training at Cendikia Vocational School, Cirebon City has proven that a new approach to the teaching and learning process is able to provide concrete solutions in overcoming the challenges of distance learning. The results of this training showed significant improvements in student engagement, the quality of learning materials, and the effectiveness of communication between teachers and students. In addition, the use of technology and digital media has enabled wider and more flexible learning accessibility for students, even in difficult times like these. However, active commitment and cooperation from all relevant parties is needed to ensure the continuity and improvement of this learning innovation. Support from schools, parents and local governments in providing adequate facilities and infrastructure, as well as ongoing training for teachers in the use of technology are important factors in the successful implementation of this innovation.